Comparison of growth and aflatoxin B1 production profiles of Aspergillus flavus strains on conventional and isogenic GM-maize-based nutritional matrices. Issue 1 (January 2022) - Gasperini, Alessandra M.; Medina, Angel; Magan, Naresh
Abstract: Maize grown in both North and South America are now predominantly genetically modified (GM) cultivars with some resistance to herbicide, pesticide, or both. There is little information on the relative colonisation and aflatoxin B1 (AFB1 ) production with maize meal-based nutritional matrices based on kernels of non-GM maize and isogenic GM-ones by strains of Aspergillus flavus . The objectives were to examine the effect of interacting conditions of temperature (25–35 °C) and water availability (0.99–0.90 water activity, aw ) on (a) mycelial growth, (b) AFB1 production and (c) develop contour maps of optimum and marginal conditions of these parameters for four strains of A. flavus on three different non-GM and isogenic GM-maize based nutritional media. The growth of the four strains of A. flavus (three aflatoxigenic; one non-aflatoxigenic) was relatively similar in relation to the temperature × aw conditions examined on both non-GM and GM-based matrices. Optimum growth overall was at 30–35 °C and 0.99 aw for all four strains. Under water stress (0.90 aw ) growth was optimum at 35 °C. Statistically: non-GM, GM cultivars, temperature and aw all significantly affected growth rates. For AFB1 production, all single and interacting factors were statistically significant except for non-GM × GM cultivar. In conclusion, colonisation of GM- and non-GM nutritional sources was similar for the different A. flavus strains examined. The contour maps will be very useful for understanding the ecological niches for both toxigenic and non-toxigenic strains in the context of the competitive exclusion of those producing aflatoxins. Highlights: Aspergillus flavus strains grew similarly on GM/non-GM nutritional media under interacting abiotic factors Contour maps of optimum and marginal conditions for growth were developed for 4 strains of A. flavus Aflatoxin B1 production was optimal at 0.99 water activity and 30 °C, regardless of strain. Optimum and marginal toxin production contour maps were determined for toxigenic strains